2019
DOI: 10.1017/s0022215119000380
|View full text |Cite
|
Sign up to set email alerts
|

Implementing a guideline for acute tonsillitis using an ambulatory medical unit

Abstract: ObjectiveAcute tonsillitis represents a significant proportion of admissions to ENT departments nationally. Given current hospital pressures, it is vital to look for safe alternatives to admission. This study explores the safe management of patients in an ambulatory medical unit, without the need for admission.MethodsA retrospective review of 48 patients’ notes was carried out. Following the development and implementation of a guideline for acute tonsillitis, a prospective re-audit of 41 patients was carried o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
(13 reference statements)
1
1
0
Order By: Relevance
“…Perkins et al . 7 also showed similar results with their protocol, halving the length of admission and more than halving the admission rate. Larger studies have similarly demonstrated a decrease in admission rate with the introduction of an ambulant management pathway.…”
Section: Resultssupporting
confidence: 56%
See 1 more Smart Citation
“…Perkins et al . 7 also showed similar results with their protocol, halving the length of admission and more than halving the admission rate. Larger studies have similarly demonstrated a decrease in admission rate with the introduction of an ambulant management pathway.…”
Section: Resultssupporting
confidence: 56%
“…This approach has been validated by Harris and Ashman 6 who demonstrated a 42 per cent early discharge rate in patients treated with a similar protocol, with zero re-admissions. Perkins et al 7 also showed similar results with their protocol, halving the length of admission and more than halving the admission rate. Larger studies have similarly demonstrated a decrease in admission rate with the introduction of an ambulant management pathway.…”
Section: Tonsillitismentioning
confidence: 64%